Early care and support for young children with developmental disabilities and their caregivers in Uganda: The Baby Ubuntu feasibility trial - Nanyunja, Carol; Sadoo, Samantha; Kohli-Lynch, Maya; Nalugya, Ruth; Nyonyintono, James; Muhumuza, Anita; Katumba, Kenneth R.; Trautner, Emily; Magnusson, Brooke; Kabugo, Daniel; Cowan, Frances M.; Zuurmond, Maria; et al. (Frontiers in Pediatrics, 2022)
Abstract Background: Early care and support provision for children with developmental disabilities is frequently lacking, yet has potential to improve child and family outcomes, and is crucial for promoting access to healthcare and early education. We evaluated the feasibility, acceptability, early impact and costs of the Baby Ubuntu participatory, peer-facilitated, group program for young children with developmental disabilities and their caregivers in Uganda. Methods: A feasibility trial, with two parallel groups, compared Baby Ubuntu with standard care. Caregivers and children, aged 6-11 months with moderate-severe neurodevelopmental impairment, were recruited and followed for 12 months. Quantitative and qualitative methods captured information on feasibility (ability to recruit), acceptability (satisfactory attendance), preliminary evidence of impact (family quality of life) and provider costs. Results: 126 infants (median developmental quotient, 28.7) were recruited and randomised (63 per arm) over 9 months, demonstrating feasibility; 101 (80%) completed the 18-month follow-up assessment ( 9 (7%) died, 12 were lost to follow up, 4 withdrew)during follow-up. Of 63 randomised to the intervention, 59 survived (93%); of theseing children randomised to intervention, 51 (86%) attended ≥6 modules, meeting acceptability criteria, and 49 (83%) completed the 18 month follow-up assessment. Qualitatively, Baby Ubuntu was feasible and acceptable to caregivers and facilitators. Enabling factors included community sensitisation by local champions, positive and caring attitudes of facilitators towards children with disability, peer support, and the participatory approach to learning. Among 101 (86%) surviving children seen at 12 months, mixed methods evaluation provided qualitative evidence of impact on family knowledge, skills, and attitudes, however impact on a scored family quality of life tool was inconclusive. Barriers included stigma and exclusion, poverty, and the need to manage expectations around the child’s progress. Total provider cost for delivering the program per participant was USD 232 per participant. Conclusions: A pilot feasibility trial of the Baby Ubuntu program found it to be feasible and acceptable to children, caregivers and healthcare workers in Uganda. A mixed methods evaluation provided rich programmatic learning including qualitative, but not quantitative, evidence of impact. The cost estimate represents a feasible intervention for this vulnerable group, encouraging financial sustainability at scale.